ENTITIES OF LOCAL SELF-GOVERNMENT AS POSSIBLE HOLDERS OF HUMAN RIGHTS - Боштјан Тратар (Годишњак Правног факултета у Бањалуци)
In this article, the author, using the scientific method of comparison and analysis, presents the case law regarding position of municipalities and other self-governing local communities as entities of public law as potential human rights holders. These self-governing local communities generally share the principled position of entities of public law, to which the legal order recognizes (merely) the status of the addressee of human rights, not the holder. From the constitutional case law of some European countries (Germany, Liechtenstein, Switzerland), especially Slovenia, and the United States of America, as a representative of the Anglo-Saxon legal system, it follows that local communities are recognized as holders of human rights either by enforcing the so-called procedural human rights (as this does not require a link with exercising dignity of an individual) and property rights or the right to filing the so-called municipal constitutional complaints when it comes to enforcing protection of local selfgovernment against unconstitutional interference with the constitutional right to local self-government. The author believes that the development of titularity of municipalities in relation to human rights, i.e. municipalities as holders of human rights, is often subject to legal policy.